A disease model resource reveals core principles of tissue-specific cancer evolution - Sebastian Mueller; Niklas de Andrade Krätzig; Markus Tschurtschenthaler; Miguel G. Silva; Chiara Thordsen; Riccardo Trozzo; Perrine Simon; Frederic Saab; Thorsten Kaltenbacher; Magdalena Zukowska; Daniele Lucarelli; Rupert Öllinger; et al. (Nature, 2026)
Abstract Oncogenes such as KRAS display marked tissue specificity in their oncogenic potential, genetic interactions and phenotypic effects, but the underlying determinants remain largely unresolved 1–5 . Here, to address these questions, we developed the Mouse Cancer Cell line Atlas, a broad-utility resource of 590 comprehensively characterized models across a wide range of entities ( www.mcca.tum.de ). Comparative and functional studies using this platform, human cohorts and mice identified core principles underlying tissue-specific evolution of KRAS -initiated cancers. First, we show that mutant KRAS dosage gain through allelic imbalance exerts cell-type-specific effects, defining its timing across entities, as exemplified by dosage-sensitive developmental reprogramming during pancreatic cancer initiation. Second, we highlight how tissue- and stage-specific evolutionary requirements, such as block of differentiation in the intestine, select for KRAS -collaborating alterations. Third, we identified context-dependent epistatic KRAS –tumour suppressor interactions and show that reciprocal dosage sensitivities dictate the entity-specific patterns of cancer gene alterations, explaining their frequency, zygosity and acquisition chronology. These findings highlight how intrinsic and acquired determinants instruct cancer evolution in different tissues, with predictable molecular patterns, temporal dynamics and phenotypic outcomes. Our study provides major advances towards a mechanistic understanding of cancer genomes.